2017
DOI: 10.1371/journal.pgen.1006647
|View full text |Cite
|
Sign up to set email alerts
|

dMyc is required in retinal progenitors to prevent JNK-mediated retinal glial activation

Abstract: In the nervous system, glial cells provide crucial insulation and trophic support to neurons and are important for neuronal survival. In reaction to a wide variety of insults, glial cells respond with changes in cell morphology and metabolism to allow repair. Additionally, these cells can acquire migratory and proliferative potential. In particular, after axonal damage or pruning the clearance of axonal debris by glial cells is key for a healthy nervous system. Thus, bidirectional neuron-glial interactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…In addition to its cell growth regulatory role, dMyc is also required to prevent JNK pathway activation during retinal glial cell development [ 51 ]. In salivary glands, physiological JNK activation takes place during pupal stages and is part of the disintegration process of the gland [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its cell growth regulatory role, dMyc is also required to prevent JNK pathway activation during retinal glial cell development [ 51 ]. In salivary glands, physiological JNK activation takes place during pupal stages and is part of the disintegration process of the gland [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the JNK pathway, however, dHUWE1 and dMyc exhibit reciprocating functions: While dHUWE1 inhibits JNK activation, dMyc enhances JNK activation in salivary gland cells. This is likely a context-specific function of dMyc, as dMyc was shown to antagonize the JNK pathway during retinal glial cell development [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the Myc family transcription factors in regulation of glial plasticity, potency, and function appears to be evolutionarily conserved in the deuterostome lineage (Tavares et al , ). For example, the vertebrate ortholog of Myc, c‐Myc, has been demonstrated to control the potency of radial glial cells.…”
Section: Radial Glia In Neural Regenerationmentioning
confidence: 99%
“…In all x-z scans apical cells were up and anterior cells were left. promotes cell migration by activating JNK signaling (Ma et al, 2017a;Tavares et al, 2017). Here, overexpression of salr/SALL4 led to a downregulation of the dMyc level in the dpp-Gal4 domain (Fig.…”
Section: Dmyc Is Repressed By Sal/sall4mentioning
confidence: 79%
“…MYC restrains breast cancer cell motility and invasion through transcriptional silencing of integrin subunits (Liu et al, 2012). In Drosophila, dMyc inhibits JNK signaling in retinal progenitors to block non-autonomous glia over-migration (Tavares et al, 2017). The Drosophila puc gene, encoding the sole JNKspecific MAPK phosphatase and inhibitor (Martin-Blanco et al, 1998), and its mammalian homologue Dusp10 are directly bound by Myc as shown in ChIP-sequencing data (Yang et al, 2013;Sabò et al, 2014).…”
Section: Discussionmentioning
confidence: 97%